Yield and fruit quality of ’Chimarrita’ and ’Maciel’ peaches on different rootstocks - Galarça, Simone Padilha; Fachinello, José Carlos; Betemps, Débora Leitzke; Machado, Nicácia Portella; Haas, Luciane Both; Prezotto, Marcos Ernani; Comiotto, Andressa (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the influence of rootstocks on fruit postharvest quality and productivity of the peach cultivars 'Chimarrita' and 'Maciel'. The experiment was carried out in the Municipalities of Bento Gonçalves, Eldorado do Sul, and Capão do Leão, in the state of Rio Grande do Sul, Brazil, during three years. The rootstocks 'Aldrighi', 'Capdeboscq', 'Flordaguard', 'Nemaguard', 'Okinawa', and 'Mume' were evaluated. The plants were conducted using the “V” system, with 1.5x5.0 m spacing. The following variables were evaluated: fruit mass and diameter, number of fruit per plant, yield per plant, production efficiency, pulp firmness, and contents of soluble solids. The analyzed variables were little influenced by rootstocks, on the three‑year production average. Cultivar Maciel had high‑production efficiency in all rootstocks. The rootstock 'Nemaguard' provided the highest yield to cultivar Maciel in Bento Gonçalves, while the rootstock Mume, the lowest production to 'Chimarrita', in Eldorado do Sul. Firmness was the fruit quality variable most influenced by the rootstocks, depending on local conditions.